2017
DOI: 10.1007/s00464-017-5884-3
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant open ventral hernia repair: what is the financial impact of performing open ventral hernia with other abdominal procedures concomitantly?

Abstract: This study noted decreased costs when combining VHR with panniculectomy or abdominoplasty and hysterectomy or oophorectomy. For removal of infected mesh and bowel resection or stoma closure, waiting, when feasible, is recommended. Given the impending changes in financial reimbursements in healthcare in the United States, it is prudent that future studies evaluate further the clinical and fiscal benefit of concomitant procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
2
1
0
2
Order By: Relevance
“…Consistent with the present findings, increased financial costs for combined ventral hernia repair and stoma closure compared with two separate procedures have been reported, thus advocating for a dual-stage approach from an economical point-of-view [ 19 ]. In the present study, data on a stoma closure prior to an incisional hernia repair was not included.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with the present findings, increased financial costs for combined ventral hernia repair and stoma closure compared with two separate procedures have been reported, thus advocating for a dual-stage approach from an economical point-of-view [ 19 ]. In the present study, data on a stoma closure prior to an incisional hernia repair was not included.…”
Section: Discussionsupporting
confidence: 88%
“…The same authors reported non-significant difference between groups regarding BMI, indicating that, BMI did not affect the choice of the operative intervention. In addition, Madabhushi et al [17] reported comparable results as the current study regarding patient age and gender; although they performed intervention in an older group [the mean age was around 53.0 years in both groups]. But both groups were statistically comparable.…”
Section: Discussionsupporting
confidence: 71%
“…Значимость данного аргумента под черкивает тот факт, что 32,8% больных после выпол нения первого этапного вмешательства на длительный срок откладывают выполнение второй операции [12]. По данным ряда исследований, этапное лечение сочетанных хирургических заболеваний сопровожда ется дополнительными эмоциональными нагрузками и финансовыми расходами, связанными с повторны ми операциями, анестезией [8,13]. Также отмечает ся меньшая удовлетворенность пациентов непосред ственными, отдаленными и косметическими результа тами этапных оперативных вмешательств [14].…”
Section: Optimization Of Surgical Treatment Of Patients With Inguinal...unclassified